Mainstreaming Dynastic Political Thought on the Website Islami.co: A Viewpoint of Hans Georg Gadamer's Hermeneutic Theory - Hidayatus Syadyya, Dini Tri; Ala, Abd; Salik, Mohamad (Mukaddimah: Jurnal Studi Islam, 2025)
The phenomenon of political dynasties, namely the inheritance of power in a particular family or group, has become an important issue in Indonesia's political dynamics and attracted the attention of the media, including Islamic-based media such as Islami.co. Islami.co articles often raise the topic of political dynasties with a perspective that links Islamic values and their relevance to contemporary political practices. Hans-Georg Gadamer's hermeneutic approach, particularly the concept of fusion of horizons, is used in this research to understand how Islami.co mainstreams the discourse of dynastic politics. Gadamer's theory emphasizes a dialogue between the text and the reader that involves the incorporation of historical, social, and cultural perspectives. Through this framework, Islami.co not only provides information, but also interprets the phenomenon of dynastic politics by linking it to Islamic history, such as the leadership of Bani Umayyah and Bani Abbasiyah, which reflects the appropriateness of traditional values in a modern context. This hermeneutic approach allows Indonesian Muslim readers to understand political dynasties in a more complex framework, not just as a practice that is viewed negatively or positively. As a result, Islami.co acts as an agent of interpretation that combines the horizon of Islamic history and current political challenges, resulting in a new understanding that balances Islamic values with contemporary political dynamics in Indonesia.